2011
DOI: 10.1021/je200759g
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(II) Complexes of Aminopolycarboxylic Ligands in Aqueous Solution

Abstract: The binding capacity of five aminopolycarboxylic ligands (APCs) [nitrilotriacetate (NTA), ethylenediamine-N,N,N′,N′-tetraacetate (EDTA), (S,S)-ethylenediamine-N,N′-disuccinic acid (S,S-EDDS), diethylenetriamine-N,N,N′,N″,N″-pentaacetate (DTPA), and triethylenetetraamine-N,N,N′,N″,N‴,N‴-hexaacetate (TTHA)] toward the palladium(II) ion was studied by potentiometric titrations (ISE-H+ electrode) in NaNO3 and in NaClO4/NaI (at different molar ratios) solutions and by spectrophotometric titrations (only in NaClO4),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 42 publications
(84 reference statements)
1
19
0
Order By: Relevance
“…Conversely, the loss of antigen-binding specificity does not appear to be an issue when using monomeric BFCAs that have smaller molecular structures, e.g., isothiocyanobenzyl-EDTA (SCN-Bn-EDTA, molecular weight (MW) 439 Da) was successfully used to conjugate CD45 antibodies with palladium isotopic cations for barcoding assays of live cells 25 . A previous study of palladium complexes of aminopolycarboxylic ligands in aqueous solution reported that DTPA complex with Pd 2+ is more stable (log K of 36.31) than EDTA complex with Pd 2+ (log K of 23.60) 48 . Therefore, in this presented protocol, monomeric BFCA of maleimidefunctionalized-DOTA was used to chelate Pd 2+ isotopic cations and was conjugated to the monoclonal antibody, as illustrated in Fig.…”
Section: Comparison Of Metal Isotope Chelation Methodsmentioning
confidence: 94%
“…Conversely, the loss of antigen-binding specificity does not appear to be an issue when using monomeric BFCAs that have smaller molecular structures, e.g., isothiocyanobenzyl-EDTA (SCN-Bn-EDTA, molecular weight (MW) 439 Da) was successfully used to conjugate CD45 antibodies with palladium isotopic cations for barcoding assays of live cells 25 . A previous study of palladium complexes of aminopolycarboxylic ligands in aqueous solution reported that DTPA complex with Pd 2+ is more stable (log K of 36.31) than EDTA complex with Pd 2+ (log K of 23.60) 48 . Therefore, in this presented protocol, monomeric BFCA of maleimidefunctionalized-DOTA was used to chelate Pd 2+ isotopic cations and was conjugated to the monoclonal antibody, as illustrated in Fig.…”
Section: Comparison Of Metal Isotope Chelation Methodsmentioning
confidence: 94%
“…Palladium concentration was checked by ICP-AES technique against Pd(NO 3 ) 2 standard solutions (Fluka) or gravimetrically using the dimethylglyoxime method. 7,8 NTA, EGTA, DTPA, HEDP, and DTPP were supplied by Fluka with analytical grade media. Both kind of measurements were done using an 809 Metrohm Titrando apparatus equipped with a combined Orion glass electrode Ross type 8102.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…In the last years our research group carried out a systematic study on the binding ability of several ligand classes having different kind of binding groups toward Pd 2+ ion and some stability data on palladium(II)−ligand complexes have already been published. 7,8 Among these ligands, five aminopolycarboxylates (APCs) having different number of amino and carboxylic groups were taken into account. The interest for this ligand class arises from their strong binding ability toward metal ions and for this reason these compounds find interesting applications in different cases in which the sequestration/ removal of some metal ions is requested.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last years, our research group undertook a systematic study on the sequestering ability of several APCs and APPs towards different metal ions of environmental and biological interest [13][14][15][16]. As a further contribution, a study on the interaction of Ag + with four APCs [nitrilotriacetic acid (NTA), ethylene-glycol-bis (2-aminoethylether Silver is a rare metal usually present in nature as mineral ore, and the most abundant is argentite.…”
Section: Introductionmentioning
confidence: 99%